Na⁺/H⁺ exchanger and myocardial growth - Cingolani, Horacio Eugenio (2005)
The stretching of a papillary muscle induces a sudden and immediate rise in force, due to an augmentation in myofilament Ca²⁺ responsiveness. During the next 10 to 15 minutes a progressive increase in force develops known as the “slow force response” (SFR), that is due to a progressive increase in Ca²⁺ transient amplitude. The source for this increase in Ca²⁺ transient remained obscure until we proposed a link between Ca²⁺ influx mediated by Na⁺/ Ca²⁺ (NCX) exchange in reverse mode and the activation of the Na⁺/H⁺ exchanger (NHE-1) caused by stretch;1-4 being the increase in the Ca²⁺ transient secondary to the increase in intracellular Na⁺ concentration ([Na+]i). It is known that the increase in [Na⁺]i can induce an increase in intracellular Ca²⁺ levels ([Ca²⁺ ]i) through the NCX either as a result of a decrease in Ca²⁺ efflux (decreased forward mode) or an increase in Ca²⁺ entry (increased reverse mode). The fact that after myocardial stretch there is no increase in diastolic [Ca²⁺ ]i 1,5 as would be expected for a decrease in Ca²⁺ efflux, suggests that the reverse mode of NCX is the mechanism involved in the increase in Ca²⁺ transient.1The SFR, the increase in [Na⁺]i and the increase in Ca²⁺ transient can be abolished by blocking the Angiotensin II (Ang II) AT1 receptors with losartan; the endothelin (ET) ETA receptors by BQ123 and by inhibition of the NHE-1.6